IMPLEMENTASI KEGIATAN EKSTRAKURIKULER KALIGRAFI DALAM MENINGKATKAN KETERAMPILAN MENULIS ARAB DI SMA IT ASY-SYADZILI PAKIS MALANG - Sinta Nur Zakiyah; Nur Hasan; Faridatus Sa'adah (VICRATINA, 2022)
This study aims to determine the planning, implementation process, and how the supporting and inhibiting factors of calligraphy extracurricular activities in improving Arabic writing skills at SMA IT Asy-Syadili. This study uses a qualitative approach with the type of case study research. The data collection procedure used observation, interviews, and documentation data. The data analysis techniques used are data reduction, data presentation, and data verification. Planning for calligraphy extracurricular activities requires various preparations, namely extracurricular goals, costs, implementation plans, coaches, required facilities, implementation schedules, and activity locations. The process of implementing calligraphy extracurricular activities at SMA IT Asy-Syadzili Pakis is carried out outside class hours, every Saturday is divided into two sessions, morning and afternoon. First, the introduction of calligraphy. Second, prepare tools/media. Then the coach starts the material by writing on the blackboard so that students can imitate it and learn to make single and continuous letters from hijaiyah letters. 3) Supporting and inhibiting factors, support from the school, support from parents, the willingness of students, and adequate infrastructure. The obstacle is that there are students who are not good at writing Arabic and have difficulty finding a disciplined calligraphy extracurricular teacher.